A unified modeling method for dynamic analysis of GPL-reinforced FGP plate resting on Winkler-Pasternak foundation with elastic boundary conditions. (15th July 2020) - Liu, Jincan; Deng, Xiaowei; Wang, Qingshan; Zhong, Rui; Xiong, Rui; Zhao, Jing
Abstract: In this paper, dynamic analysis of functionally graded porous (FGP) plate with reinforcement of graphene platelets (GPLs) resting on elastic foundation and restrained by elastic boundary condition is investigated. Four types of porous materials reinforced with four types of graphene platelets varying along the thickness direction are considered. The analytical model of the GPLs-FGP plate is formulated by the first-order shear deformation theory and the multi-segment partition technique. For each plate segment, the displacement component of translation and revolution is implemented by Jacobi polynomials. Ultimately, the dynamics of the GPLs-FGP plate analysis model is solved by the Rayleigh-Ritz method. Aimed at validating the accuracy of the present method, the analytical results are compared with the results of finite element simulations after the convergence test is completed. Based on the above investigation, series of parametric studies with regard to the free, forced vibration and transient analysis are conducted, which provide reference data for future research.